Reinforcement effect and mechanism of graphene oxide on mortar with alkali free liquid accelerator - Yang, Renhe; Zhang, Pengyu; Huang, Tianyong; Wang, Dongmei; Sun, Qian; Mao, Zhiyi; Liu, Shuang; Li, Yang; Wang, Wanshen (Construction & building materials, 2024)
This research mainly investigated the reinforcement effect of graphite oxide (GO) on mortar mixed with alkali free liquid accelerator (AF-LA).The 0.05 % GO and 8.0 % AF-LA were selected as composite additives in cement paste and mortar. Comparative tests showed that the setting time of cement paste was shorter, and the flexural and compressive strength of mortar specimen increased significantly at 1d and 28d. In addition, using XRD combined with TG and SEM analysis, the results showed that GO nanosheets and AF-LA synergistically accelerated cement hydration, especially the hydration of C3S minerals, which resulted in more characteristic portlandite (CH) crystals appearing in the hydration products. Therefore, the above results were the main reasons for the composite of GO and AF-LA to improve the mechanical properties of mortar. •The synergistic effect of GO and AF-LA on mortar performance was studied.•The composite addition of GO and AF-LA could significantly improve mortar compressive strength.•Revealed the mechanism of GO and AF-LA enhancing the mechanical strength of mortar.